The role of inorganic ions in the calcium carbonate scaling of seawater reverse osmosis systems - Waly, Tarek; Kennedy, Maria D.; Witkamp, Geert-Jan; Amy, Gary; Schippers, Jan C. (Desalination, 2012)
In supersaturated solutions the period preceding the start of ‘measurable’ crystallization is normally referred to as the ‘induction time’. This research project aimed to investigate the induction times of CaCO 3 in the presence of Mg 2+ and SO 4 2−. The prepared synthetic solutions have the same ionic strength values found in the Gulf of Oman SWRO concentrates at 30% and 50% recovery. The results showed a significant increase in the induction time by 1140%, 2820%, and 3880% for a recovery of 50%, when adding SO 4 2− only, Mg 2+ only, or both Mg 2+ and SO 4 2−, respectively, to synthetic SWRO concentrate compared to that obtained in the absence of Mg 2+ and SO 4 2− at an initial pH of 8.3. The increase in the induction time in the presence of SO 4 2− was more than likely to be due to nucleation and growth inhibition while the presence of Mg 2+ affected the nucleation and growth through both complexation and inhibition. After a 5-month solution stabilization period, ESEM and XRD analyses showed aragonite in solutions containing Mg 2+. On the contrary, calcite was the final crystal phase formed in solutions with no Mg 2+. This suggests that magnesium may play an important role in inhibiting the formation of calcite. ► The induction times of CaCO 3 in the presence of Mg 2+ and SO 4 2− was investigated. ► The presence of Mg 2+ and SO 4 2− significantly increased the induction time in. ► SO 4 2− increased the induction time through crystal growth inhibition. ► Mg 2+ affected the nucleation and growth through both complexation and inhibition. ► ESEM and XRD analyses showed that magnesium inhibited the formation of calcite.